ENZYMES ACTIVITY OF GLUTATHIONE ANTIOXIDANT SYSTEM OF CHLOROBIUM LIMICOLA IMV K-8 BACTERIA UNDER THE INFLUENCE OF COPPER (II) SULFATE - Т. Б. Сегін; С. О. Гнатуш; О. Д. Масловська; О. М. Василів (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2018)
Aim. Investigation of changes of glutathione antioxidant system enzymes activity of Chlorobium limicola ІМV K-8 bacteria under the influence of copper (II) sulfate. Methods. In this investigation there were used C. limicola ІМV K-8 bacteria which were cultivated in Green sulfur bacteria medium. Glutathione peroxidase activity was determined by the rate of oxidation of reduced glutathione before and after incubation with tert-butyl hydroperoxide by color reaction with 5,5-dithiobis-2-nitrobenzoic acid. Glutathione S-transferase activity was determined by the rate of formation of conjugate of reduced glutathione with 1-chloro-2,4-dinitrobenzene. Results. Glutathione-S-transferase, glutathione peroxidase and glutathione reductase activity of cell free extracts of C. limicola ІМV K-8 were investigated under the influence of copper (II) sulfate in concentrations that caused decrease of biomass accumulation from 10 to 70%. It was shown that under the influence of all investigated copper (II) sulfate concentrations glutathione-S-transferase and glutathione peroxidase activity increased in comparison with control. Activity of these enzymes changed in dependence on copper (II) sulfate concentration in incubation medium and duration of cultivation. Also it was determined that glutathione reductase activity is absent in investigated bacteria. Conclusion. The increase of activity of glutathione peroxidase by 2–12 times and glutathioneS-transferase by 1.5–2 times, in comparison with control, in cell free extracts of C. limicola ІМV К-8 under the influence of copper (II) sulfate indicates on accumulation of hydrophobic and hydrophilic organic peroxides inside the cells. It also shows that, possibly, this system is one of the important ways of cell defense of green photosynthetic bacteria, in particular C. limicola, against reactive oxygen species.